Determining the sample size necessary to pass the tentative final monograph pre-operative skin preparation study requirements - Paulson, Daryl S. (International Journal of Clinical Trials, 2016)
Predicting the sample size needed to pass the Food and Drug Administration’s current requirements for the preoperative skin preparation can be very difficult. The purpose of the original FDA formula is detect if the test and positive control products are different and if the test product achieves greater reductions than the control product. The new Tentative Final monograph includes specific requirements for the lower bounds of the 95% confidence interval and the 70% responder rates. To meet these requirements, it is important to first conduct a pilot study to determine whether the products will pass the 70% responder rate and then determine the correct sample size correctly to ensure the 95% confidence level is 70% or above.